2020
DOI: 10.3390/w12041048
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Sammer, M., et al. Strong Gradients in Weak Magnetic Fields Induce DOLLOP Formation in Tap Water. Water 2016, 8, 79

Abstract: The authors wish to make the following corrections to this paper [1]: In all instances mentioning “2 kG·m−1”, these gradients should be replaced by “770 G·m−1 (WCM 62081992) and 740 G·m−1 (WCM 62083545)”: Abstract, page 1, line 4; Chapter 1 [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…effects in water impacted by a magnetic field with dynamically ordered liquid-Like oxyanion polymers (DOLLOP) (3). With DOLLOP, it was shown that the gradient of the magnetic field is more essential for the effect than magnetic strength.…”
Section: Introductionmentioning
confidence: 99%
“…effects in water impacted by a magnetic field with dynamically ordered liquid-Like oxyanion polymers (DOLLOP) (3). With DOLLOP, it was shown that the gradient of the magnetic field is more essential for the effect than magnetic strength.…”
Section: Introductionmentioning
confidence: 99%